2009
DOI: 10.1186/1471-2156-10-47
|View full text |Cite
|
Sign up to set email alerts
|

Missense and nonsense mutations in melanocortin 1 receptor (MC1R) gene of different goat breeds: association with red and black coat colour phenotypes but with unexpected evidences

Abstract: BackgroundAgouti and Extension loci control the relative amount of eumelanin and pheomelanin production in melanocytes that, in turn, affects pigmentation of skin and hair. The Extension locus encodes the melanocortin 1 receptor (MC1R) whose permanent activation, caused by functional mutations, results in black coat colour, whereas other inactivating mutations cause red coat colour in different mammals.ResultsThe whole coding region of the MC1R gene was sequenced in goats of six different breeds showing differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 47 publications
(85 reference statements)
3
81
1
4
Order By: Relevance
“…DNA was extracted using a standard phenol-chloroform protocol for blood, the Wizard ® Genomic DNA Purification kit for blood and milk (Promega Corporation, Madison, WI, USA) or rapid extraction methods for milk and hair roots (Russo et al, 2007). Primers for MC1R amplification and sequencing (Table 1) were designed with Primer 3 (Whitehead Institute for Biomedical Research, Cambridge, MA, USA) from the published bovine, sheep and goat MC1R gene sequences (GenBank accession numbers: AF445641, Y13965, and FM212940, respectively; Rouzaud et al, 2000;Våge et al, 1999;Fontanesi et al, 2009a). PCR was performed using a TGradient thermal cycler (Biometra, Göttingen, Germany) or a PT-100 thermal cycler (MJ Research, Watertown, MA, USA) in a volume of 20 L containing 10-100 ng DNA template, 1 U DNA EuroTaq DNA polymerase (EuroClone Ltd., Paington, Devon, UK), 1× PCR Buffer, 2.5 mM dNTPs, 10 pmol of each primer and optimised MgCl2 concentrations (from 1.0 to 2.0 mM).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted using a standard phenol-chloroform protocol for blood, the Wizard ® Genomic DNA Purification kit for blood and milk (Promega Corporation, Madison, WI, USA) or rapid extraction methods for milk and hair roots (Russo et al, 2007). Primers for MC1R amplification and sequencing (Table 1) were designed with Primer 3 (Whitehead Institute for Biomedical Research, Cambridge, MA, USA) from the published bovine, sheep and goat MC1R gene sequences (GenBank accession numbers: AF445641, Y13965, and FM212940, respectively; Rouzaud et al, 2000;Våge et al, 1999;Fontanesi et al, 2009a). PCR was performed using a TGradient thermal cycler (Biometra, Göttingen, Germany) or a PT-100 thermal cycler (MJ Research, Watertown, MA, USA) in a volume of 20 L containing 10-100 ng DNA template, 1 U DNA EuroTaq DNA polymerase (EuroClone Ltd., Paington, Devon, UK), 1× PCR Buffer, 2.5 mM dNTPs, 10 pmol of each primer and optimised MgCl2 concentrations (from 1.0 to 2.0 mM).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…Gain of function and loss of function mutations of the MC1R gene determining dominant or partially dominant black/dark and recessive or partially recessive red/yellow/pale coat colour phenotypes, respectively, have been described in several mammals, such as mice (Robbins et al, 1993), humans (Valverde et al, 1995), cattle (Klungland et al, 1995;Joerg et al, 1996;Rouzaud et al, 2000), pigs (Kijas et al, , 2001, horses (Marklund et al, 1996), foxes (Våge et al, 1997;Våge et al, 2005), beach and pocket mice (Hoekstra et al, 2006;Nachman et al, 2003), rabbits (Fontanesi et al, 2006), and goats (Fontanesi et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Gain-of-function and loss-of-function mutations of the MC1R gene determining dominant or partially dominant black/dark and recessive or partially recessive red/yellow/pale coat colour phenotypes, respectively, have been described in a large number of mammals including, for example, mice (Robbins et al, 1993), humans (Valverde et al, 1995) and several farm animals like cattle (Klungland et al, 1995;Joerg et al, 1996;Rouzaud et al, 2000), pigs (Kijas et al, 1998 and, horses (Marklund et al, 1996), dogs (Everts et al, 2000;Newton et al, 2000), cats (Eizirik et al, 2003;Peterschmitt et al, 2009), rabbits (Fontanesi et al, 2006) and goats (Fontanesi et al, 2009a). In sheep, classical genetic studies have identified two alleles at the Extension locus: the dominant black (E D ) allele caused by two missense mutations in the MC1R gene (p.M73K and p.D121N) and present in the Norwegian Dala, Corriedale, Damara, Black Merino, Black Castellana and Karakul breeds (Vå ge et al, 1999 andRoyo et al, 2008); and the wild type (E 1 ) allele widely distributed in most breeds (Searle, 1968;Sponenberg, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Fontanesi et al (2009) characterized the variability of the caprine melanocortin receptor 1 (MC1R) gene identifying one nonsense, three missense and one silent single nucleotide polymorphisms (SNP). Unfortunately, none of these mutations showed a clear association with coat colour when analysing their segregation in a pool of 317 goats belonging to six breeds with different pigmentation patterns (Fontanesi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fontanesi et al (2009) characterized the variability of the caprine melanocortin receptor 1 (MC1R) gene identifying one nonsense, three missense and one silent single nucleotide polymorphisms (SNP). Unfortunately, none of these mutations showed a clear association with coat colour when analysing their segregation in a pool of 317 goats belonging to six breeds with different pigmentation patterns (Fontanesi et al, 2009). Moreover, sequence analysis of the caprine agouti signaling protein (ASIP) gene has evidenced the existence of a duplicated copy, as previously demonstrated in sheep (Norris and Whan 2008), and three missense SNP.…”
Section: Introductionmentioning
confidence: 99%